A CD Study of a Structure-Based Selection of N-Heterocyclic Bis-Carbene Gold(I) Complexes as Potential Ligands of the G-Quadruplex-Forming Human Telomeric hTel23 Sequence - Maria Marzano; Filippo Prencipe; Pietro Delre; Giuseppe Felice Mangiatordi; Gabriele Travagliante; Luisa Ronga; Gennaro Piccialli; Michele Saviano; Stefano D’Errico; Diego Tesauro; Giorgia Oliviero (Molecules)
Herein, we report the structure-based selection via molecular docking of four N-heterocyclic bis-carbene gold(I) complexes, whose potential as ligands for the hTel23 G-quadruplex structure has been investigated using circular dichroism (CD) spectroscopy, CD melting, and polyacrylamide gel electrophoresis (PAGE). The complex containing a bis(1,2,3,4,6,7,8,9-octahydro-11H-11λ3-pyridazino[1,2-a]indazol-11-yl) scaffold induces a transition from the hybrid (3 + 1) topology to a prevalent parallel G-quadruplex conformation, whereas the complex featuring a bis(2-(2-acetamidoethyl)-3λ3-imidazo[1,5-a]pyridin-3(2H)-yl) moiety disrupted the original G-quadruplex structure. These results deserve particular attention in light of the recent findings on the pathological involvements of G-quadruplexes in neurodegenerative diseases.